Exploring the Social and Cultural Dimensions of Learning for Recent Engineering Graduates during the School-to-Work Transition. Issue 2 (4th May 2021) - Lutz, Ben; Paretti, Marie C.
Abstract : The school-to-work transition is a challenging period for engineering graduates. In contrast to most engineering curricula, workplace learning involves organizations, people, cultures, and a range of non-technical and technical elements. Where many researchers have focused on skills gaps across school and work, we focus here on contexts gaps, or shifts in learning processes across organizational settings. Using reflective journals and semi-structured interviews, we explored significant learning events during recent engineering graduates' school-to-work transition. Using theories of organizational socialization, we characterize significant experiences related to social and cultural dimensions of participants' new organizational roles. Newcomers in this study reported learning related to, for example, forming relationships, learning local language, interacting with power structures, and other features of their organizations. Results offer points of contrast in which we compare learning processes and highight critical differences across school and workplace settings. Findings suggest that engineering educators should consider the broad spectrum of learning that takes place as graduates transition to their new professional roles. By better understanding the role of context in organizational learning, educators can more effectively prepare recent graduates for contemporary practice and develop a deeper appreciation for the interconnectedness of the social, cultural, and technical dimensions of engineering work.